2017
DOI: 10.1016/j.jarmac.2017.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Believing is seeing: Biased viewing of body-worn camera footage.

Abstract: Body-worn camera (BWC) footage is expected to be objective, thereby improving transparency. But can other information about an incident affect how people perceive BWC footage? In two experiments, we examined the effects of officer-generated misinformation and outcome information on people’s memory for an event. Participants viewed BWC footage and/or read an officer’s report containing misleading information. Some participants learned the officer was punished, some that the citizen was arrested. Participants th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 43 publications
4
37
0
3
Order By: Relevance
“…For almost every dependent variable, the extent to which people reported to identify with the police predicted their responses. This finding is consistent with previous research examining how people consider police encounters (Granot et al, ; Jones et al, , ). However, in Study 2, IPS was not always a significant predictor.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…For almost every dependent variable, the extent to which people reported to identify with the police predicted their responses. This finding is consistent with previous research examining how people consider police encounters (Granot et al, ; Jones et al, , ). However, in Study 2, IPS was not always a significant predictor.…”
Section: Discussionsupporting
confidence: 92%
“…The attention instruction did not attenuate or exacerbate people's judgments of the officer or the civilian. Finally, participants who read the officer's police report containing misleading information provided responses that were more favorable for the officer and less favorable for the civilian, replicating the results of Jones et al (). For Study 2, we focus on the role that more specific, directive instructions might have in attenuating the positive bias that BWC footage affords officers.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…This understanding of use of force creates ample opportunity for debate around whether a use‐of‐force incident was legally justifiable versus illegal and excessive. One might think that evaluations of the reasonableness of police use of force would be made easier in the BWC era, but research demonstrates that interpretations of video footage are connected to pre‐existing beliefs, challenging the presumption that video produces objective assessments of what is observed (Jones, Crozier, & Strange, , ). Bearing in mind that videos are interpreted through our own biased individual lenses, and that videos depicting police use of force are inherently evocative, it is important to explore the effect of BWC evidence relative to other media of evidence presentation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Little research explores how exposure to BWC footage affects public perceptions. Studies by Jones et al (, ) found that interpretation of BWC footage is influenced by officer statements that present misinformation (which could happen intentionally through lying or unintentionally through flawed recollection) and observers' pre‐existing attitudes toward police. Both variables serve to undermine assumptions that video footage always serves as objective, stand‐alone evidence.…”
Section: Literature Reviewmentioning
confidence: 99%